Review: recent trends in management of oral lichen planus - Garg, Shubhangi; Malik, Sangeeta S.; Kamarthi, Nagaraju; Goel, Sumit; Gupta, Swati (International Journal of Basic & Clinical Pharmacology, 2023)
Oral lichen planus (OLP) is a chronic mucocutaneous inflammatory disease, associated with altered cell‐mediated immunological function. It has been characterised by long‐term evolution, repeated exacerbations, sometimes painful and resistant to treatment, or even all of these. OLP significantly affects quality of patient's life. There is a higher risk of malignant transformation accompanied with OLP and similar appearing oral lichenoid lesions. Current OLP therapy aims at eliminating all mucosal‐related lesions reduce symptomatology and decrease the risk of oral cancer. This review summarizes recent treatment modalities used in the management of OLP which includes corticosteroids, immunomodulatory agents, retinoids, ultraviolet irradiation and/or laser therapy, herbal remedies. In addition, focus is also given upon adopting holistic approach in such patients by emphasizing on stress management.